DEVELOPMENT OF INDONESIAN CAKE DIGITAL BOOK BASED ON LOCAL WISDOM FOR CULINARY EDUCATION STUDENTS - Mutiara, Erli; Anugerah, Ajeng Inggit; Sutanti, Siti; Humairah, Erfiani (Jurnal Ilmiah Teunuleh, 2022)
Digital books or commonly called E-Books which stands for Electronic Books are paperless books, where e-books are easily accessible through Personal Digital Assistants (PDAs) or special bags made by information technology companies. This study uses a research and development (R&D) approach which is then adapted to the needs of researchers which includes six stages, namely (1) preliminary survey; (2) preparation of electronic teaching materials using the Kvisoft Flipbook Maker application, product design; (4) design validation;(5) design improvement; and (6) description of research results. The purpose of this research is to develop a digital book of Indonesian cakes based on local wisdom for culinary education students. Data collection techniques used expert validation questionnaires and small-scale trials. The results of the development of the textbook show that the average validation and test results are in the appropriate category for use with good predicates according to the table of eligibility criteria and product revisions.